Life, subjectivity & art : Essays in honor of rudolf bernet - Melle, Ullrich; Breeur, Roland (Phaenomenologica, Published Under the Auspices of the Husserl-Archives, 2012)
This is the first and only collection of essays honoring the work of Rudolf Bernet, a philosopher of worldwide authority. The essays are centered on three major themes of Bernet's philosophical itinerary: life, seen from a phenomenological point of view, its relation to subjectivity, experiences and consciousness, and both seen as the ground for an original reflection on art, specifically paintings. The contributors are eminent phenomenologists and scholars closely related to Rudolf Bernet, as person and as philosopher: colleagues, friends and collaborators, former students. Taken as a whole, this volume is a testiment to Bernet's philosophical inspiration and influence, and the enduring importance of his own books, articles and classes.